1997
DOI: 10.1159/000259264
|View full text |Cite
|
Sign up to set email alerts
|

Transtympanic Electro-cochleography in the Assessment of Perilymphatic Fistulas

Abstract: An objective method for the pre-operative diagnosis and the post-operative assessment of a presumed perilymphatic fistula (PLF) using transtympanic electrocochleography is presented. Three cases are reported in which the history of the disease and the symptoms strongly suggested the presence of a PLF. Pre-operative transtympanic electrocochleography (TT ECoG) recordings at rest showed changes similar to those of endolymphatic hydrops and signs of instability of the inner ear hydrodynamic system during raised i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
1
2
0
1
Order By: Relevance
“…20 Transtympanic electrocochleography showed a low sensitivity. 21,22 The present study revealed no false positive ␤-TP results. The mean value of ␤-TP in positive samples was 23.5 mg/l.…”
Section: Discussionsupporting
confidence: 46%
“…20 Transtympanic electrocochleography showed a low sensitivity. 21,22 The present study revealed no false positive ␤-TP results. The mean value of ␤-TP in positive samples was 23.5 mg/l.…”
Section: Discussionsupporting
confidence: 46%
“…In animal models of meningitis, there is evidence that CSF changes early in the disease are transmitted to the inner ear and explain early hearing loss. 13 The close relationship between CSF and the inner ear fluid is well illustrated by perilymph fistula presenting with vertigo because of endolymphatic hydrops 14 15 and the rarer ‘stapes gusher’ recognised by ENT surgeons. A case showing imaging evidence of endolymphatic hydrops in spontaneous intracranial hypotension has been published.…”
Section: Relations Between Csf and The Inner Earmentioning
confidence: 99%
“…The decision is usually based on the clinical impression in combination with the standard diving decompression tables. One possibility for detecting a perilymphatic fistula preoperatively is the use of a transtympanic electrocochleography during raised intrathoracic pressure or with postural changes (12,13).…”
Section: Arterial Air Applicationmentioning
confidence: 99%